Moda e sociedade $h [recurso eletrônico] : $b representações da estética e das indumentárias na revista Kodak (1912-1915) - Silveira, Daniele Deise Antunes (2015)
Based on the understanding that fashion is a media that expresses and assign meanings to periods, regions and cultures, this research aims to study fashion published in Kodak magazine in the period 1912 to 1915, through the analysis of images and texts, to identify how the social changes of the end nineteenth century and beginning of the twentieth century articulate to build specifics looks, reinforced and spread in the magazine. The period is marked in Brazil, the entry of amounts called European modernity in all sectors of society, and in the fashion it is visible the influences as the parisian Belle Epoque as the resulting changes, especially before tensions to War world. The configuration of new urban habits, developed from the restructuring of the capital, inspired, especially in Paris, contributes to the press to develop, adopting other formats, and reaching new readers, according to the ideas of the modern world. In the sense, in Porto Alegre - RS, the Kodak magazine illustrated varieties, stood out as a publication that contributed to the remodeling of existing social standards, informing about the news and often building a civilizing discourse. The study has as main object of analysis printed photos in the magazine, but also used of the articles and advertising that somehow recall the theme of fashion. For the achievement the analysis, the photos were divided into two main categories: studio photographs, and street photographs, subdivided in menswear and womenswear. This division allows us to identify a reality explicitly built through the scenarios and compositions produced in the studios, and another, which although also built, allows a more relationship with the lived experience, from some implicit attributes observed in the images, in general defined as "glaring". Analysis revealed, in general aspect, a clothing coming permeated by elements of Portuguese colonization, the other due to the development of techno-scientific revolution of the period as well as the adoption of values linked to European modernity. As regards the differences between male and female dress, there was the adoption of French models for women and English for men, both reflected especially in the studio photographs, while those who had the backdrop of the street They showed major changes with respect to European benchmarks.